2019
DOI: 10.1563/aaid-joi-d-18-00253
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Effects on Human Gingival Fibroblasts

Abstract: Strontium is a naturally occurring alkaline earth metal that has been shown to be useful not only in the treatment and prevention of osteoporosis but also in the treatment of dentinal hypersensitivity in the oral cavity; strontium is also an effective cariostatic, antiplaque, antigingivitis agent. Relatively little is known, however, about the effects of strontium on gingival fibroblasts. The purpose of the present investigation was to conduct in vitro studies on the potential for strontium to positively affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…This explained why the hydrogels with SrRan showed higher cell viability when compared with hydrogels without SrRan addition. The same effect of a strontium-containing drug on fibroblast growth was observed by Fernandes et al (2019) who concluded that strontium citrate increases the human gingival fibroblast activity. Er et al (2008) also observed that SrRan does have a favorable effect on fibroblast cells at low concentrations.…”
Section: Resultssupporting
confidence: 68%
“…This explained why the hydrogels with SrRan showed higher cell viability when compared with hydrogels without SrRan addition. The same effect of a strontium-containing drug on fibroblast growth was observed by Fernandes et al (2019) who concluded that strontium citrate increases the human gingival fibroblast activity. Er et al (2008) also observed that SrRan does have a favorable effect on fibroblast cells at low concentrations.…”
Section: Resultssupporting
confidence: 68%
“…HGF cells in the study were provided by Dr. Visser (Oral Biology Department, University at Buffalo) (IRB number 663292‐1) after being isolated from gingival tissue collected from a healthy patient with no clinical periodontal disease as previously described 18 . Tissue was acquired with approval for research use from the university's Institutional Review Board with written consent obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Strontium is considered one of the potential candidates for orthopedic applications in that this element can promote the growth of osteoblast cells [150][151][152]. A certain amount of Sr in Mg alloys can enhance the corrosion resistance [153] and mechanical strength of the alloys [154].…”
Section: LImentioning
confidence: 99%